ANALISIS YURIDIS TERHADAP PERTIMBANGAN HAKIM DALAM MEMBERIKAN DISPENSASI NIKAH DIBAWAH UMUR DI PENGADILAN AGAMA KABUPATEN MALANG KELAS 1A - Ahmad Fauzan Mubarok; Ahmad Subekti; Shofiatul Jannah (Jurnal Hikmatina, 2022)
Marriage in Indonesia is regulated in Law No. 16 of 2019 concerning the age limit for prospective grooms and brides to be at least 19 years old. This requires that people who will perform marriages be aged by applying for a marriage dispensation in the Religious Court. In this case the judge of the Religious Court may grant or even refuse such dispensation as per the judge's consideration. In consideration the judge must lead to the benefit of reducing the hypocrisy that will occur in the future